New Ways to Treat Tuberculosis Using Dendrimers as Nanocarriers - Serge Mignani; Rama Pati Tripathi; Liang Chen; Anne-Marie Caminade; Xiangyang Shi; Jean-Pierre Majoral (MDPI AG, 2018)
Tuberculosis (TB) is a contagious infection that usually attacks not only the lungs, but also brain and spine. More than twenty drugs have been developed for the treatment of TB, but most of them were developed some years ago. They are used in different combinations. Isoniazid and Rifampicin are examples of the five first line TB drugs, whereas, for instance, Levofloxacin, Kanamycin and Linezolid belong to the second line drugs that are used for the treatment of drug resistant TB. Several new bicyclic nitroimidazoles (e.g., Delamanid) without mutagenic effects were developed. New TB drugs need to provide several main issues such as more effective, less toxic, and less expensive for drug resistant TB. Besides polymeric, metal-based nanoparticles, polymeric micelles and polymers, dendrimer nanostructures represent ideal delivery vehicles and offer high hopes for the future of nanomedicine. In this original review, we present and analyze the development of anti-TB drugs in combination with dendrimers. Few articles have highlighted the encapsulation of anti-TB drugs with dendrimers. Due to their unique structure, dendrimers represent attractive candidates for the encapsulation and conjugation of other anti-TB drugs presenting important drawbacks (e.g., solubility, toxicity, low bioavailability) that hinder their development, including clinic trials.